Why Do Firms Announce Open-Market Repurchase Programs? - Oded, Jacob (Review of Financial Studies, 2005)
Empirically, a price increase accompanies the announcement of an open-market stock repurchase program, even though the announcement is not a commitment. In fact, for many announced programs no shares are ever actually repurchased. This article explores this puzzle. In the single-firm-type version of the model, the option that a firm grants itself by announcing a program does not generate announcement returns. In equilibrium, long-run gains from the informed trading that the option creates are offset by short-run costs from the market's accounting for this adverse selection. Based on this trade-off, I construct a signaling (two-type) model that can deliver announcement returns. In the separating equilibrium, good firms do not incur any cost when they announce programs. Their gains from informed trading in the long run offset the cost of announcement incurred in the short run. Mimicry is costly, because a bad firm's long-run gains from informed trading cannot compensate for the short-run cost of announcing.